Social media use and anti-immigrant attitudes: evidence from a survey and automated linguistic analysis of Facebook posts - Ahmed, Saifuddin (2022)
Social media has a role to play in shaping the dynamic relations between immigrants and citizens. This study examines the effects of threat perceptions, consumptive and expressive use of social media, and political trust on attitudes against immigrants in Singapore. Study 1, based on a survey analysis (N = 310), suggests that symbolic but not realistic threat perception, is positively associated with anti-immigrant attitudes. The consumptive use of social media and political trust is negatively related to anti-immigrant attitudes. Moderation analyses suggest that consumptive social media use has negative consequences for individuals with increased symbolic threat perception and high political trust. But is there a correspondence between consumptive and expressive use of social media in terms of predicting prejudicial attitudes? Study 2 benchmarks the survey findings against participants’ opinion expression via Facebook posts (N = 146,332) discussing immigrants. Automated linguistic analyses reveal that self-reported survey measures correlate with the expressive use of social media for discussing immigrants. Higher anti-immigrant attitudes are associated with higher negative sentiment, anger, and swear words in discussing immigrants. The findings highlight the need to pay attention to the combined influence of social media use and individual political beliefs when analyzing intergroup relations.